Diccionario de derecho civil [ES] - Arco Torres, Miguel Ángel del; Pons González, Manuel (Comares, 1999)
Keywords: Ciencias sociais e humanas; Dereito; Dereito civil; Dicionario terminolóxico; Español (Lingua); Terminoloxía

Diccionario jurídico y económico [ES] - Becher, Herbert J. (C.H. Beck'sche Verlagsbuchhandlung, 1999)
Keywords: Administración; Ciencias sociais e humanas; Dereito; Dicionario terminolóxico; Español (Lingua); Terminoloxía

Black's law dictionary [EN] - Black, Henry Campbell; Garner, Bryan A. (West Group, 1999)
Keywords: Administración; Ciencias sociais e humanas; Dereito; Dicionario terminolóxico; Inglés (Lingua); Terminoloxía

Traducir para la justicia [ES] - Feria García, Manuel C. (Comares, 1999)
Keywords: Administración; Ciencias sociais e humanas; Dereito; Dicionario terminolóxico; Español (Lingua); Terminoloxía; Tradución

Dictionnaire de droit privé [FR] - Puigelier, Catherine (Éditions Larcier, 1999)
Avec plus de 2400 définitions en droit civil, droit pénal, droit commercial, droit du travail, procédure civile, procédure pénale… le Dictionnaire de droit privé est un outil absolument indispensable pour l’étudiant(e) de Droit ou d’AES ou le professionnel du Droit. Les termes importants comprennent, en plus de la définition principale, une explication complémentaire qui inclut des exemples, des références de jurisprudence, de doctrine, permettant ainsi d’avoir une vision complète du terme défini. Indispensable pour maîtriser parfaitement le langage juridique.
Keywords: Administración; Ciencias sociais e humanas; Dereito; Dicionario terminolóxico; Francés (Lingua); Terminoloxía

The New Palgrave Dictionary of Economics and the Law [EN] - Newman, Peter (Palgrave Macmillan UK, 1998)
A great deal of economics is about law - the functioning of markets, property rights and their enforcement, financial obligations, and so forth - yet these legal aspects are almost never addressed in the academic study of economics. Conversely, the study and practice of law entails a significant understanding of economics, yet the drafting and administration of laws often ignore economic principle. The New Palgrave Dictionary of Economics and the Law is uniquely placed by the quality, breadth and depth of its coverage to address this need for building bridges. Drawn from the ranks of academics, professional lawyers, and economists in eight countries, the 340 contributors include world experts in their fields. Among them are Nobel Laureates in economics and eminent legal scholars. The New Palgrave Dictionary of Economics and the Law will become a benchmark for reference of the highest quality.
Keywords: Administración; Ciencias sociais e humanas; Dereito; Dicionario terminolóxico; Economía; Inglés (Lingua); Terminoloxía

Léxico jurídico para periodistas [ES] - Alarcón Gonzálvez, Carmen (Servicio de Publicaciones, Fundación Universitaria San Pablo CEU, 1998)
Keywords: Ciencias sociais e humanas; Dereito; Dicionario terminolóxico; Español (Lingua); Léxico; Terminoloxía; Xornalismo

Formularios de actos y contratos [ES] - Álvarez de Morales y Ruiz, Antonio (Biblioteca Comares de ciencia jurídica, 1998)
Keywords: Ciencias sociais e humanas; Dereito; Español (Lingua); Formularios; Terminoloxía

Fachsprache Recht: Hauptbd [DE] - Beltrán-Gandullo, Milagros; Bitzenhofer, Torsten H. (Dürr und Kessler, 1998)
Keywords: Alemán (Lingua); Ciencias sociais e humanas; Dereito; Dicionario terminolóxico; Terminoloxía

Dictionary of Law [EN] - Curzon, Leslie Basil (Financial Times/Pitman Pub., 1998)
Intended for students and practising legal professionals. Entries are substantial and are often enhanced by statutory definitions, judicial pronouncements and maxims, extracted from law reports, statutes and other branches of legal literature.*Major revision and enlargement to cover four years of legislative developments (over 200 new statutes) and new cases*Comprehensive entries on all aspects of English law*Clear, concise definitions of specialised legal terminology and jargon, including Latin terms*Extensively cross-referenced, giving full references for all cases and statutes, and full list of law report abbreviations
Keywords: Administración; Ciencias sociais e humanas; Dereito; Dicionario terminolóxico; Inglés (Lingua); Terminoloxía

Diccionario do seguro en lingua galega [GL] - López Taboada, Carme (Xunta de Galicia, Dirección Xeral de Política Lingüística. Winterthur Ibérica AEIE, 1998)
Keywords: Administración; Ciencias sociais e humanas; Dereito; Dicionario terminolóxico; Finanzas; Galego (Lingua); Terminoloxía

Routledge Spanish dictionary of business, commerce and finance: Spanish-English, English-Spanish [EN, ES] - Muñiz Castro, Emilio Germán (Routledge, 1998)
Keywords: Administración; Ciencias sociais e humanas; Comercio; Dereito; Dicionario terminolóxico; Economía; Empresa; Español (Lingua); Finanzas; Inglés (Lingua); Terminoloxía

Diccionario Trivium de derecho y economía [ES] - Robles, Federico Carlos Sáinz de (Editorial Trivium, 1998)
Keywords: Administración; Ciencias sociais e humanas; Dereito; Dicionario terminolóxico; Español (Lingua); Terminoloxía

Introducción al Derecho inglés y norteamericano [ES] - Séroussi, Roland; Alcaraz Varó, Enrique (Ariel derecho, 1998)
Keywords: Ciencias sociais e humanas; Dereito; Documentación; Español (Lingua); Estados Unidos; Gran Bretaña; Terminoloxía

Lenguaje jurídico [ES] - Aguirre Beltrán, Blanca; Hernando de Larramendi, Margarita (Sociedad General Española de Librería, 1997)
This work covers both the written & oral communication skills necessary for professionals. The text includes authentic documents, questions & exercises, an answer key, a list of abbreviations & a multilingual glossary. A well-presented, easy to use manual for professionals, students & teachers alike!
Keywords: Ciencias sociais e humanas; Dereito; Español (Lingua); Linguaxe; Terminoloxía

Curso superior de linguaxe xurídica para funcionarios da administración de xustiza [GL] - López Taboada, Carme (Xunta de Galicia, Dirección Xeral de Xustiza e Interior, 1997)
Keywords: Administración; Ciencias sociais e humanas; Dereito; Dicionario terminolóxico; Galego (Lingua); Terminoloxía

Vocabulario xurídico, aforismos e locucións latinas [ES, GL, LA] - Rodríguez Ennes, Luis (Universidade de Vigo-Servicio de Publicacións, 1997)
Keywords: Administración; Ciencias sociais e humanas; Dereito; Dicionario terminolóxico; Español (Lingua); Galego (Lingua); Latín (Lingua); Terminoloxía; Vocabulario

Introducción a la traducción jurídica y jurada (francés-español): orientaciones metodológicas para la realización de traducciones juradas y de documentos jurídicos [ES, FR] - San Ginés Aguilar, Pedro; Ortega Arjonilla, Emilio (Interlingua (Comares), 1997)
Keywords: Ciencias sociais e humanas; Dereito; Documentación; Español (Lingua); Francés (Lingua); Tradución

Dictionnaire du droit privé français [FR] - Braudo, Serge; Baumann, Alexis (OVH, 1996)
Keywords: Administración; Ciencias sociais e humanas; Dereito; Dicionario terminolóxico; Francés (Lingua); Terminoloxía

Formularios procesales civiles [ES] - Rodríguez Hermoso, Francisco (Comares, 1996)
Keywords: Ciencias sociais e humanas; Dereito; Español (Lingua); Formularios; Terminoloxía

Rechtswörterbuch: Spanisch-Deutsch, Deutsch-Spanisch: mit Erläuterungen, Darstellungen von Gesetzen, Verordnungen, Verträgen, Abkürzungen, Gerichtsverfassungen, Rechtsbehelfen/Diccionario jurídico: español-alemán, español-alemán: con explicaciones de leyes, reglamentos, contratos, abreviaturas, organizaciones judiciales, recursos [DE, ES] - Rothe, Martin (Luchterhand, 1996)
Keywords: Administración; Alemán (Lingua); Ciencias sociais e humanas; Dereito; Dicionario terminolóxico; Español (Lingua); Terminoloxía

Collins Dictionary of Law [EN] - Stewart, William J; Burgess, Robert (Harper Collins, 1996)
Keywords: Administración; Ciencias sociais e humanas; Dereito; Dicionario terminolóxico; Inglés (Lingua); Terminoloxía

Introducción al derecho para no juristas [ES] - Valpuesta Gastaminza, Eduardo (Eunate, 1996)
Keywords: Ciencias sociais e humanas; Dereito; Documentación; Español (Lingua); Terminoloxía

Formularios de herencias [ES] - Álvarez de Morales y Ruiz, Antonio; Arco Torres, Miguel Ángel del (Comares, 1995)
Keywords: Ciencias sociais e humanas; Dereito; Español (Lingua); Formularios; Terminoloxía

Dictionnaire de termes juridiques en quatre langues / Diccionario jurídico en cuatro idiomas / Legal dictionary in four languages / Rechtswörterbuch in vier Sprachen [DE, EN, ES, FR] - Le Docte, Edgard (Civitas ; Maklu Vitgevers ; Nomos ; Schulthess Polygraphischer verlag, 1995)
Keywords: Administración; Alemán (Lingua); Ciencias sociais e humanas; Dereito; Dicionario terminolóxico; Español (Lingua); Francés (Lingua); Inglés (Lingua); Terminoloxía

Formulario de actas notariales [ES] - Simó Santonja, Vicente L. (Comares, 1995)
Keywords: Ciencias sociais e humanas; Dereito; Español (Lingua); Formularios; Terminoloxía

Dictionnaire droit, science politique, économie, gestion, comptabilité, fiscalité [FR] - Bichot, Jacques; Martin, Michel-Louis; Guiho, Pierre (L'Hermès, 1994)
Keywords: Administración; Ciencias sociais e humanas; Comercio; Dereito; Dicionario terminolóxico; Economía; Empresa; Finanzas; Francés (Lingua); Política; Terminoloxía

Manual de linguaxe administrativa [GL] - García Cancela, Xermán; Díaz Abraira, Carlos (Manuais (Escola Galega de Administración Pública), 1994)
Keywords: Administración; Ciencias sociais e humanas; Dereito; Dicionario terminolóxico; Galego (Lingua); Manual; Terminoloxía

Lexique juridique, économique et de gestion : français-espagnol, espagnol-français [ES, FR] - Garnot, Pierre Yves; Guerrini, Mauro; Rabade-Lucero, A. (1994)
Keywords: Administración; Ciencias sociais e humanas; Comercio; Dereito; Dicionario terminolóxico; Economía; Empresa; Español (Lingua); Finanzas; Francés (Lingua); Léxico; Terminoloxía

Rechtswissenschaft: Lese- und Arbeitsbuch [DE] - Jung, Lothar (Max Hueber, 1994)
Keywords: Alemán (Lingua); Ciencias sociais e humanas; Dereito; Dicionario terminolóxico; Terminoloxía

A Dictionary of Law [EN] - Martin, Elizabeth A. (Oxford paperback reference, 1994)
Keywords: Administración; Ciencias sociais e humanas; Dereito; Dicionario terminolóxico; Inglés (Lingua); Terminoloxía

Diccionario de términos jurídicos [ES] - Martínez Marín, Jacinto; Ávila Martín, María del Carmen (Comares, 1994)
Keywords: Administración; Ciencias sociais e humanas; Dereito; Dicionario terminolóxico; Español (Lingua); Terminoloxía

Formularios de poderes [ES] - Simó Santonja, Vicente L.; Simó Sevilla, Vicente (Comares, 1994)
Keywords: Ciencias sociais e humanas; Dereito; Español (Lingua); Formularios; Terminoloxía

Dictionnaire juridique: français-espagnol / Diccionario jurídico: español-francés. Navarre [ES, FR] - Amorós Rica, Narciso; Merlin Walch, Olivier (Librairie générale de droit et de jurisprudence, 1993)
Keywords: Administración; Ciencias sociais e humanas; Dereito; Dicionario terminolóxico; Español (Lingua); Francés (Lingua); Terminoloxía

Experiencias jurídicas y teoría del derecho [ES] - Díez-Picazo, Luis (Ariel, 1993)
Keywords: Ciencias sociais e humanas; Dereito; Documentación; Español (Lingua); Terminoloxía

Diccionario bilingüe de terminología jurídica: inglés-castellano, castellano-inglés [EN, ES] - Mazzucco, Patricia Olga; Hebe Maranghello, Alejandra (Abeledo-Perrot, 1992)
Keywords: Administración; Ciencias sociais e humanas; Dereito; Dicionario terminolóxico; Español (Lingua); Inglés (Lingua); Terminoloxía

Manual de estilo del lenguaje administrativo [ES] - Ministerio para las Administraciones Públicas (Ministerio para las Administraciones Públicas, 1991)
Keywords: Administración; Ciencias sociais e humanas; Español (Lingua); Manual; Terminoloxía

Léxico da Administración castelán-galego [ES, GL] - Real Academia Galega; Instituto da Lingua Galega (Real Academia Galega, 1991)
Keywords: Administración; Ciencias sociais e humanas; Dereito; Dicionario terminolóxico; Español (Lingua); Galego (Lingua); Léxico; Terminoloxía

Black's Law Dictionary: Definitions of the Terms and Phrases of American and English Jurisprudence, Ancient and Modern [EN] - Black, Henry Campbell; Nolan, Joseph R. (West Publishing Company, 1990)
First published in 1891, Black's is now in a 6th edition that reflects changes in tax, finance, commerce, health care, environmental and criminal law. Terms are listed alphabetically with cross-references, and entries give basic legal definitions, word usages, citations, and pronunciation. Entries range in length from one sentence to multiple-pages with subdivisions. Appendices include a copy of the Constitution, a time chart, of Supreme Court membership, and an organizational chart of the federal government. This is not only a standard reference tool for law, but an important supplement to all high school social studies courses. Also available in a 1992 abridged edition.
Keywords: Administración; Ciencias sociais e humanas; Dereito; Dicionario terminolóxico; Inglés (Lingua); Terminoloxía

Diccionario terminológico de economía, comercio y derecho = Dictionary of economic, business and legal terminology: english/spanish-spanish/english-inglés/español-español/inglés [EN, ES] - Muñiz Castro, Emilio-Germán (Biblioteca de terminología hispánica. Colección diccionarios, 1990)
Keywords: Administración; Ciencias sociais e humanas; Comercio; Dereito; Dicionario terminolóxico; Economía; Empresa; Español (Lingua); Inglés (Lingua); Terminoloxía